Synergistic influences of BMP9 and NGF on the osteogenic differentiation of C3H10T1/2 mesenchymal stem cells - Junyu Liu; Kun Yang; Gang Li; Yinghui Tan (Journal of Orthopaedic Surgery and Research)
Abstract Background Bone morphogenetic protein 9 (BMP9) and nerve growth factor (NGF) are critical factors influencing osteogenic differentiation in mesenchymal stem cells (MSCs). While BMP9 has been recognized for its potent osteogenic capabilities, NGF’s role in bone tissue engineering is less understood. This investigation delineated the synergistic link of BMP9 with NGF in driving osteogenic differentiation in C3H10T1/2 MSCs. Objective To evaluate the combined impact of BMP9 and NGF on osteogenic markers’ expression levels and the formation of calcified nodules in C3H10T1/2 cells, providing a basis for the enhanced bone regeneration strategies in tissue engineering. Methods C3H10T1/2 cells were subjected to treatment regimens incorporating NGF at variable concentrations (10, 50, and 100 ng/ml) and BMP9, either as monotherapies or in combination. Osteogenic differentiation’ comprehensive assessment was undertaken by quantifying early-stage markers (Runx2, Col I) and late-stage markers (OPN) via RT-PCR, Western blotting, ALP staining, and Alizarin Red S staining for mineralized matrix deposition. Results NGF elicited a concentration-dependent augmentation of early osteogenic markers, with the 10 ng/ml dosage demonstrating maximal efficacy. BMP9 independently facilitated robust osteogenic differentiation, whereas the combinatorial treatment with BMP9 and NGF synergistically amplified the expression levels of Runx2, Col I, and OPN. Notably, this combined treatment yielded a remarkable enhancement in the deposition of mineralized extracellular matrix, as evidenced by a notable escalation in the size and density of calcified nodules relative to monotherapies. Conclusion The findings unveiled the remarkable synergistic link of BMP9 with NGF in potentiating osteogenic differentiation in C3H10T1/2 MSCs. This dual-factor approach presents a compelling paradigm for advancing bone regeneration strategies, providing substantial promise for utilization in bone tissue engineering plus regenerative medicine.